2015
DOI: 10.17576/jsm-2015-4401-09
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight Relationship and Condition Factor of Fish Populations in Temengor Reservoir: Indication of Environmental Health

Abstract: Length-weight relationship (LWR) and condition factor of seven fish species from the Temengor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 18 publications
1
16
0
4
Order By: Relevance
“…Bu çalışma ile aynı zamanda balıkçılık idaresi ile çalışanlara koruma. rehabilitasyon gibi ileride yapılacak çeşitli ekolojik çalışmalara da katkıda bulunacaktır [29]. Genel olarak bir balık büyümesinin tespit edilmesinde boy artışıyla beraber ağırlık artışının da hesaplanması gerekir.…”
Section: Tartişma Ve Sonuç (Discussion and Conclusion)unclassified
“…Bu çalışma ile aynı zamanda balıkçılık idaresi ile çalışanlara koruma. rehabilitasyon gibi ileride yapılacak çeşitli ekolojik çalışmalara da katkıda bulunacaktır [29]. Genel olarak bir balık büyümesinin tespit edilmesinde boy artışıyla beraber ağırlık artışının da hesaplanması gerekir.…”
Section: Tartişma Ve Sonuç (Discussion and Conclusion)unclassified
“…The 'K' value in this study (K > 0.56) indicated that L. chinensis was in good condition of well-being. The 'K' value was strongly correlated to LWR, therefore, the b value was essential to assess the wellbeing of fish (Hamid et al 2015). Therefore higher K indicated good feeding conditions for squid and it depends on seasonal changes and geographical differences.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistical analysis was conducted by calculating the mean values of the length-weight relationship and the relative condition factor of Beardless barb and Bronze featherback throughout the sampling periods because of these factors affecting the lengthweight relationship, such as habitat and seasonal effect. Stomach fullness, maturity stage, age, and sex were not considered (Hamid et al, 2015).…”
Section: Length-weight Relationship and Relative Condition W = Al Bmentioning
confidence: 99%